Dysosmia syndrome in COVID-19, сlinic, treatment and prevention - V. V. Skvortsov; V. B. Petrunicheva; D. I. Rodin (Лечащий Врач)
Background. Dysosmia is a group of various disorders of the olfactory analyzer, manifested by an increase or decrease in the ability to perceive odors, up to a complete loss of olfactory sensitivity. Until recently, the problem of olfactory impairment was not as urgent as it became in 2019 and 2020, when the whole world faced a pandemic caused by the SARS-CoV-2 virus. Such interest of doctors and researchers in olfactory dysfunction can be explained by the very high incidence of dysosmia associated with COVID-19 – 60-80% of the total number of cases among the European population and 30% among the population of East Asia. Most often olfactory function recovers spontaneously on the background of treatment of the underlying disease, usually within one month, and does not require additional therapeutic measures. As early as on day 8-9, up to 70% of patients notice an improvement in their sense of smell, and 80-90% of patients regain their sense of smell after two weeks. However, about 10-15% of patients have to turn to specialists for lack of sense of smell for 20 days or more. The presence of anosmia for more than 15-20 days is probably due to possible damage to olfactory receptor cells themselves, which can take up to 2 months to recover.Conclusion. Since the olfactory function plays a large role in the life of every person, its loss can lead to discomfort, stress and limitation of various kinds of pleasures associated with the perception of smells, etc. In addition, the inability to distinguish odors can lead to poisoning with expired products or other harmful substances. Also, dysosmia associated with COVID-19 is of particular interest, since it has a specific neurosensory mechanism of occurrence associated with damage to the cells of the olfactory neuroepithelium. Therefore, it is necessary to develop an effective treatment plan for this complication of COVID-19 infection and conduct preventive education of the entire population.